2017
DOI: 10.1038/s41598-017-08922-x
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Intervention is Effective in Creating Smoke-Free Homes for Newborns: A Randomized Controlled Trial Study in China

Abstract: Mobile-phone-based smoking cessation intervention has been shown to increase quitting among smokers. However, such intervention has not yet been applied to secondhand smoke (SHS) reduction programs that target smoking parents of newborns. This randomized controlled trial, undertaken in Changchun, China, assessed whether interventions that incorporate traditional and mobile-phone-based education will help create smoke-free homes for infants and increase quitting among fathers. The results showed that the abstin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(102 citation statements)
references
References 34 publications
(24 reference statements)
0
99
0
1
Order By: Relevance
“…Electronic and hand searching identified 550 records, with 493 references remaining after the removal of duplicates. Based on title and abstract screening, 103 relevant articles were retrieved for full-text assessment, with the final inclusion of 16 primary controlled trials [ 5 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] (associated with 41 articles, Table S1 ). Twelve of these trials had previously been identified by Behbod and colleagues [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic and hand searching identified 550 records, with 493 references remaining after the removal of duplicates. Based on title and abstract screening, 103 relevant articles were retrieved for full-text assessment, with the final inclusion of 16 primary controlled trials [ 5 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] (associated with 41 articles, Table S1 ). Twelve of these trials had previously been identified by Behbod and colleagues [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Full trial characteristics are shown in Table S2 (including population, sample size, details of the intervention and control, outcome measures, and process indicators). Twelve trials [ 5 , 38 , 39 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 ] were randomised controlled trials (RCTs), three were cluster RCTs [ 40 , 50 , 51 ], and one was a non-randomised controlled trial [ 43 ]. Most trials were conducted in the USA [ 5 , 40 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 51 ], with the remaining trials in China [ 38 , 39 , 41 , 52 ], Germany [ 46 ], and Spain [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the six papers that assessed efforts to test smoke-free home interventions involving fathers, all but one were conducted in Asian countries (three in China, one in India, one in Iran) [33,[41][42][43][44], with the remaining study conducted in Turkey [45]. Three were randomised controlled trials (RCT) assessing the feasibility of providing families with different counselling/educational interventions [41,44,45]. Two studies used a repeated cross-sectional design to assess the impacts of a ban on smoking in public places on home-smoking levels comparing pre-and post-ban survey data and home-smoking behaviour [42,43].…”
Section: Interventionsmentioning
confidence: 99%
“…One RCT conducted in China (Changchun) [44] assessed whether an intervention that incorporated traditional and mobile-phone based education could assist families in creating a smoke-free home for infants. Non-smoking mothers of newborns and fathers received counselling at the same time, which facilitated spousal interaction and support, and encouraged the mothers to be the change agents.…”
Section: Education and Mobile-health Interventionsmentioning
confidence: 99%
“…[17][18][19] Intervention strategies include home visits and fairly intensive telephone counseling, with messages often focused on cessation combined with actions to reduce smoking in the home. 14,15,16,17,[19][20][21][22][23][24] With the exception of a pediatric office-based intervention 15 few interventions to reduce SHS exposure have been replicated or widely disseminated.…”
Section: Introductionmentioning
confidence: 99%